IMMUNOLOGICAL CROSSFIRE: ENDOCRINOPATHIES IN THE AGE OF IMMUNE CHECKPOINT INHIBITORS - Sarvanandan, Tharsini; Ooi, Ying Guat; Khoo, Jun Kit; Lim, Quan Hziung; Hee, Nicholas Ken Yoong; Vethakkan, Shireene; Lim, Lee-Ling; Paramasivam, Sharmila; Ratnasingam, Jeyakantha (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Pembrolizumab is a PD1 receptor inhibitor which is a type of immune checkpoint inhibitor (ICI) for cancer therapy. Immune-related adverse events (IRAE) are more commonly encountered with increased use. CASE A 52-year-old male with recurrent renal cell carcinoma developed endocrinopathies following pembrolizumab. After failure of first-line treatment, he received the first dose of pembrolizumab in November 2022. Six weeks later, he was symptomatic of hyperthyroidism with corresponding biochemistry of TSH <0.01 m IU/L (reference interval 0.55 – 4.8), free T4 of 28.8 pmol/L (reference interval 11.5 – 22.7) and free T3 of 9.7 pmol/L (reference interval 3.5 – 5.5). Following treatment with low dose and tapering carbimazole for eight weeks, he quickly became hypothyroid. Biochemistry showed TSH of 87.3 m IU/L, fT4 of 2.9 pmol/L and fT3 of 1.3 pmol/L. Anti-thyroid peroxidase and anti-thyroglobulin antibodies were negative. Carbimazole was discontinued and levothyroxine 50 mcg daily were commenced. Pembrolizumab was continued. Four months later, he presented with lethargy and postural symptoms. A random serum cortisol level was undetectable at <14 nmol/L (reference interval 145 – 619) and ACTH level was inappropriately normal at 6 pg/ml (reference interval 0 – 46). He denied any polyuria, polydipsia, or symptoms of mass effect. His gonadal function, prolactin and electrolytes were normal. There was marked clinical improvement following hydrocortisone replacement. MRI of the pituitary gland was completely normal. A diagnosis of ICI-induced hypophysitis and thyroiditis was made. He completed the nine cycles of pembrolizumab as initially planned with good cancer response. He remains well on levothyroxine and hydrocortisone replacement. CONCLUSION This case illustrates the typical sequelae of ICI-induced endocrinopathy of thyroiditis that occurred earlier and hypophysitis later. All patients in ICI should be monitored at close intervals for hormonal dysfunction and replaced as required.